Open for business: Project-specific value capture strategies of architectural firms - Bos-de Vos, Marina (A+BE | Architecture and the Built Environment, 2018)
Architectural firms can be regarded as creative professional service firms. As such, architects need to navigate creative, professional and commercial goals, while simultaneously attempting to fulfil client, user and societal needs. This complex process is becoming increasingly difficult, as the historically established role of architects has become more blurred, contested and heterogeneous. While attempting to reclaim their role or to take on new roles in collaborations with other actors, architectural firms are challenged to develop business models that are financially viable and professionally satisfactory. These business models need to facilitate firms in capturing both financial and professional value in co-creation processes, and they must also suit the project-based structure of the firm. This research contributes insights into how firms might capture multiple dimensions of value in project-based work. It generates new perspectives on processes of organizational value capture and business model design, and provides concrete, practical insights into the difficulties of and opportunities involved in value capture by creative professional service firms. Context and approach of the research This research adopts a project-specific business model perspective (Kujala et al., 2010; Wikström et al., 2010) and multidimensional perspective on value to investigate the value capture strategies of architectural firms. While paying attention to the unique project contexts in which firms operate and the multiple dimensions of value they aim to capture, the purpose is to generate a better understanding of how firms attempt to capture value in order to attain their strategic goals. The research also aims to facilitate architectural firms and other organizations in dealing with the value capture challenges they face in practice. To reach these two objectives, two main research questions are addressed: How do architectural firms capture value in construction projects? How can architectural firms be supported in developing strategies for value capture? Drawing on 40 case-based interviews with architects and clients from 24 recently completed construction projects, as well as observational data from 17 project-oriented strategy meetings, the value capture strategies of architectural firms are examined both in retrospect and as they unfolded in practice. The empirical insights were synthesized in a toolkit that can be used by firms to engage in projects and manage their value capture activities in these projects with greater awareness. Through the adoption of an engaged scholarship approach (Van de Ven, 2007), the researcher’s background and continued involvement in architectural practice helped to assure the scientific and practical relevance of the research. Findings Three types of project-specific value capture strategies were identified: Strategies to negotiate one’s role in a project Strategies to capture value in the project-based interaction with a client Strategies to attain firm goals in a project Strategies to negotiate one’s role in a project By negotiating a certain role in a project, architectural firms attempt to shape the conditions for value capture in it. Different roles are associated with different opportunities to capture value, as certain activities or responsibilities may or may not allow firms to appropriate monetary or professional value. A boundary work lens (Gieryn, 1983; Gieryn, 1999) was used to investigate role negotiation strategies. The analysis indicates that architects use different strategies to negotiate the boundaries of their professional role, as they have different perceptions of what their professional expertise means when collaborating with other project actors. It was found that firms attempted to reinstate their role boundaries and return to the established situation when they felt that their professional expertise was not being valued. In addition, architects were found to bend their role boundaries to take on activities and responsibilities which were tailored to project demands when they considered their expertise to be constantly changing. Firms were also found to pioneer role boundaries and pursue an active break with the established situation when they considered their expertise as more broadly applicable. This shows that professional expertise plays a key part in firms’ role negotiation strategies and influences the value capture opportunities that firms might create in projects. These findings suggest that firms can improve their role negotiation strategies and how they capture value in a project by considering the expertise they have and wish to employ in the project, and by determining whether or not this expertise fits the specific project context and needs of the client. Strategies to capture value in the project-based interaction with a client Investigation of architectural firms’ project-based interactions with clients with regard to ‘use value’, ‘exchange value’ (Bowman and Ambrosini, 2000; Vargo et al., 2008) and ‘professional value’ showed that architectural firms tend to prioritize the capture of professional values over exchange value and sometimes even use value. It was found that to attain their professional goals, such as maintaining or enhancing their reputation, work pleasure and continued development, firms spent more time on activities than they were paid for, provided certain activities for free, or refrained from renegotiating the fee, thereby trading off monetary value for professional value. By delivering additional quality, which was of no value to the client, firms traded off the realization of use value for the client for professional value. This shows how architectural firms were willing to sacrifice their own capture of monetary value or the use value for the client when they recognized that their professional goals might possibly become endangered. It also emphasizes the importance of professional value in architectural firms’ value capture. The trade-offs between different value dimensions demonstrate how the hierarchy in value capture goals plays a crucial part in the value capture strategies of architectural firms. While enabling firms to capture one dimension of value, it will constrain them in the capture of another value dimension. This suggests that firms may benefit from working towards value capture strategies that are able to generate a better balance between different values in a project. Strategies to attain firm goals in a project The understanding of the value capture process of architectural firms was further supplemented by providing insights into the dynamics occurring between a project and the firm. Three kinds of value capture strategies were identified at the intersection between project and firm: Postponing financial revenues in a project (referred to as the postponing strategy) Compensating for loss of financial revenue across projects (referred to as the compensating strategy) Rejecting a project (referred to as the rejecting strategy) Examination of the strategies on the basis of the interaction of use value, exchange value and professional value revealed that firms adopted three types of value slippage responses in their projects: Taking the risk of financial value slippage Accepting financial value slippage Counteracting professional value slippage With the postponing and compensating strategies, firms risked or accepted the slippage of financial value in a project. This means that firms engaged in projects that required an initial investment, or even remained unprofitable, and created more use value than they were paid for in these projects. The slippage of financial value that resulted from this decision was often considered beneficial, as it allowed the enhanced attainment of professional goals in the longer term. While firms sometimes considered financial value slippage as potentially beneficial, professional value slippage was always prevented by firms. With the rejecting strategy, firms counteracted the slippage of professional value in projects and avoided creating use value that could not be captured as professional value or that could even harm the firm’s professional resources. The strategies and associated value slippage responses highlight that value capture is largely influenced by a firm’s willingness to take financial and professional risks in a project. The findings also indicate that firms do not necessarily aim for optimally balanced value capture in each project, but regularly accept or pursue ‘off-balance’ projects to attain higher end goals at the organizational level and over the longer term. Business model strategizing The business model strategizing process that architectural firms employ was studied to determine how firms arrive at their project-specific value capture strategies. Observations of 17 strategy meetings at architectural firms demonstrated that firm members developed their value capture strategies around professional values, thereby strengthening organizational identity but constraining innovation in their business models. Although actors jointly considered strategic alternatives in the strategy process, they often feared that these alternatives might be at odds with their professional values and beliefs. This typically triggered them to remain loyal to proven value capture strategies. These findings reveal how the three aspects of expertise, goals and risks, which influence firm role negotiation and value capture strategies, are strongly related to professional identity, thereby emphasizing the importance of professional identity in the development of value capture strategies by architectural firms. This suggests that greater awareness of the most salient aspects of professional identity may help firms to reject projects that are fundamentally not aligned with their values and to develop value capture strategies that respect professional values for the projects in which they do engage. Value capture toolkit The empirical findings on how firms attempt to capture multiple dimensions of value in projects were translated into a toolkit for value capture in projects. The toolkit was specifically designed to ensure the well-balanced integration of professional identity, expertise, goals and risks in a project. A well-balanced integration facilitates firms in selecting projects on the basis of a role that is in line with their identity. It also helps firms to capture both financial and professional value on the basis of firm expertise and risks, and thereby attain their organizational goals. The value capture toolkit consists of four main components: An overview of four generic professional role identities of architectural firms to specify the project and professional context in which one is involved. A board game with cards to develop comprehensive and balanced value capture strategies for projects by answering questions around eight core aspects involved. An overview of role identity-specific value capture challenges and recommendations to identify common pitfalls and opportunities for the type of role identity one has in a project. Example projects for each of the four generic role identities to inspire practitioners and support the generation of well thought through strategies. The toolkit can be used by architectural firms and other actors to analyse, monitor and improve their value capture strategies in projects. It supports actors to substantiate different strategic decisions in relation to one another in a structured fashion. This helps firms to arrive at more consciously developed and encompassing value capture strategies that can be better managed over the course of a project. The toolkit stimulates joint discussion and deliberation, which may provide firms with productive settings to develop new strategies while safeguarding the professional values and standards that are at stake. Conclusions and implications The investigation of architectural firms’ strategies and strategy making for project-based value capture showed that capturing multiple dimensions of value in projects is a highly complex process that is shaped by responses to tensions originating in the different contexts in which the firm is embedded. While the inter-organizational project context may give rise to tensions between a firm’s desired and actual role in a collaboration with other actors, the professional context generates tensions in the balance of different value dimensions within and across projects. The threefold theoretical implications of the research are outlined below. First, this research extends the existing literature on organizational value capture (Bowman and Ambrosini, 2000; Lepak et al., 2007; Pitelis, 2009), more specifically by project-based firms (Laursen and Svejvig, 2016) by uncovering how dynamics between different values influence the value capture strategies of firms. While the existing literature on organizational value capture has solely focused on the capture and slippage of financial value, this research demonstrates that to study the value capture of firms with multiple strategic goals, value capture and value slippage theories need to be developed around multiple value dimensions. Second, the research contributes to the literature on the management of architectural firms (Winch and Schneider, 1993) and other project-based, creative professional service firms by providing an integrative understanding of the tensions involved in the value capture of these firms and how these are dealt with. The insights gained underline the importance of developing project or solution-specific business models (Kujala et al., 2010; Wikström et al., 2010) and suggest that research on the management of creative professional service firms may benefit from additional project-specific insights into how firms co-create and capture value on a day-to-day basis. Third, the research contributes insights into how firm members jointly design business models in a project context and are influenced by the project and professional context in which they are embedded. The research shows that although actors consider innovations in their business models, professional norms and values constrain innovation. The identification of three key aspects – goals, expertise, and risks – that shape project-specific or solution-specific business model designs, from both the perspective of the project and the perspective of the firm, adds new insights to previous studies concerned with the design of business models (Zott and Amit, 2010) and the existing literature on project-specific business models (Kujala et al., 2010; Kujala et al., 2011; Wikström et al., 2010). Thorough consideration and continuous adaptation of the goals, expertise and risks in relation to organizational identity and project conditions help strengthen the power of the business model with respect to attaining intended goals. For architectural firms and other creative and/or professional service firms, the insights from this research and the toolkit developed will provide new means to develop and adopt more value-oriented and business-minded approaches in their projects. By facilitating the iterative development of project-specific value capture strategies, they allow firms to assess the benefits and risks of potential projects and jointly improve the conditions for value capture in these projects. Insights into the value capture process and trade-offs that practising architects must confront can also help architecture students to become successful professionals and entrepreneurs. Thus, by providing a better understanding of project-based value capture and fostering a desire to improve this process, this research facilitates creative professionals in developing and maintaining sustainable organizations that support the realization of unique, creative visions for advancing our society.